Proceedings of the 11th International Congress for Applied Mineralogy (ICAM) - Dong, Faqin (Springer Geochemistry/Mineralogy, 2015)
These proceedings comprise the peer-reviewed contributions submitted to the 11th International Congress for Applied Mineralogy (ICAM) held July 5-10, 2013, at the Southwest University of Science and Technology (SWUST) in Mianyang, China. The biennial ICAM is the most important gathering of applied mineralogists, organized every other year by the ICAM-Council. The multidisciplinary research presented in this book will be of interest to scientists and professionals dealing with topics like environmental and medical mineralogy; industrial minerals; bio-minerals and biomaterials; advanced materials; process mineralogy; mining and metallurgy; cultural heritage; the interaction of minerals with microorganisms; and solid waste treatment and recycling, including genetic mineralogy. "The field of applied mineralogy has been able to match society's pace by continuously reinventing itself, quickly adopting new technologies and instrumentation as they became available and putting them to work for the service of mankind living in a world that heavily relies on minerals. Over the past few decades, applied mineralogy has evolved into a cutting- edge discipline that leads the way for science, engineering and research and development to benefit society. Contrary to popular belief, mineral resources are limited, and we have an obligation to our heirs to use them responsibly." Dr. Maarten A.T.M. Broekmans Post-President ICAM Council.